Migrating Words, Migrating Merchants, Migrating Law : Trading Routes and the Development of Commercial Law. - Gialdroni, Stefania (Legal history library., 2019)
"Migrating Words, Migrating Merchants, Migrating Law examines the connections that existed between merchants' journeys, the languages they used and the development of commercial law in the context of late medieval and early modern trade. The book, edited by Stefania Gialdroni, Albrecht Cordes, Serge Dauchy, Dave De ruysscher and Heikki Pihlajamäki, takes advantage of the expertise of leading scholars in different fields of study, in particular historians, legal historians and linguists. Thanks to this transdisciplinary approach, the book offers a fresh point of view on the history of commercial law in different cultural and geographical contexts, including medieval Cairo, Pisa, Novgorod, Lübeck, early modern England, Venice, Bruges, nineteenth century Brazil and many other trading centers. Contributors are Cornelia Aust, Guido Cifoletti, Mark R. Cohen, Albrecht Cordes, Maria Fusaro, Stefania Gialdroni, Mark Häberlein, Uwe Israel, Bart Lambert, David von Mayenburg, Hanna Sonkajärvi, and Catherine Squires".